(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2024)
Studies show that political awareness is higher in Indian states and in states like the north Indian state of Rajasthan as compared to other parts of the country. A good university education and success in life has become a barrier. A better life depends on higher education. Therefore, the implications for India are immense. In this article, we attempt to analyze the trends in higher education in India and assess their impact on knowledge studies and politics. It determines not only the level of personal well-being but also the health and safety of the country as a whole. As a rule, the ideology that governs a country also affects the education system. Education allows people to participate in discussions and thus to have access to a wide range of information on various subjects. Well-educated people are more likely to be successful and usually have better political knowledge than less educated people. These experiences develop the student’s political skills and sense of efficacy, which increases his or her likelihood of participation, thus increasing his or her knowledge and skills, and leading to continued cooperation.